Artificial Propagation of Pomadasys hasta (Bloch, 1790): A Key to Reach Sustainable Aquaculture - Shawon Ahmmed; Mizanur Rahman Washim; AKM Shafiqul Alam Rubel; Debashis Kumar Mondal; Md. Hashmi Sakib; Yahia Mahmud; Md. Latiful Islam (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Reproduction of Pomadasys hasta was studied in captivity to establish an induced breeding protocol and larvae rearing tactics. Three distinct hormones viz., human chorionic gonadotropin (HCG), luteinizing hormone-releasing hormone analogues (LHRHa) and salmon gonadotropin hormone-releasing hormone (S-GnRHa) were injected to matured brooders in treatment 1 (T1), treatment 2 (T2) and treatment 3 (T3) but only 0.9% NaCl used in T4 as a control. In each treatment, three experimental trails, E1 (♀40:♂20 µg.kg-1), E2 (♀50:♂25 µg.kg-1) and E3 (♀60:♂30 µg.kg-1) were conducted along with three replications of each trail in order to optimize the hormone dose for the target species. The obtained results have aroused much attention as this is the first breakthrough on induced breeding of a grunter in the Indian subcontinent. Variation in fertilization rate, latency period, egg output and hatching rate in response to different treatments and trails were revealed here. Spawning was occurred between 33-48 h of injection in all the experiments at 17-25°C water temperature. Above all, the highest fertilization (95.45±2.34) and hatching (75.45±4.07) rates were observed in E2 of T2. After 22-26 h of fertilization, the larvae emerged from the egg membrane and the newly hatched larvae were 1.6-1.8 mm in length. Turning larvae into juveniles was noticed by 40–45 days post-hatch (dph) with scales on the entire body surface. The total length was recorded as 43.5±2.1 mm and average body weight as 0.7±0.2 g at 95 dph. This investigation unlocked a track for producing seed of P. hasta in a commercial hatchery for a sustainable aquaculture without hampering their wild stock.